Instrumentalizing the Expressive: Transplanting Sentencing Circles into the Canadian Criminal Trial - Goldbach, Toby S. (2015)
This Article examines reforms to criminal sentencing procedures in Canada, focusing on Aboriginal healing circles, which were incorporated as sentencing circles into the criminal trial. Using the lens of comparative law and legal transplants, this Article recounts the period of sentencing reform in Canada in the 1990s, when scholars, practitioners, and activists inquired into Aboriginal confrontation with the criminal justice system by comparing Euro-Canadian and Aboriginal justice values and principles. As a way to bridge the gap between vastly differing worldviews and approaches to justice, judges and Aboriginal justice advocates transplanted sentencing circles into the sentencing phase of the criminal trial. This Article presents original data compiled from a review of all published decisions in Canada that mention the term sentencing circle. It reviews judicial treatment of requests for sentencing circles, and tracks sentencing decisions once a circle was held. Additionally, this Article uses sentencing circles as a point of entry into conversations about legal instrumentalism in law reform and legal transplants. It argues that the progress of these reforms points to larger questions about culture and what it currently means to use law as a tool for social change